Distributional and welfare effects of replacing monetary benefits with universal basic income in Spain - Nuria Badenes Plá; Borja Gambau-Suelves; María Navas Román (University of Essex, Institute for Social and Economic Research (ISER), 2019)
This papers quantifies the redistributive effects on progressivity, poverty and welfare, that would occur if the monetary benefits currently in place in the Spanish system were to be replaced by a neutral alternative in terms of spending, granting a universal basic income (UBI) to everyone. We have calculated two scenarios: one in which the benefit system is replaced by a basic income, and another in which retirement pensions are maintained, with the rest of monetary benefits being distributed via a UBI. The simulations are carried out using EUROMOD. The implementation of a UBI, even a very radical one that eliminates the existing benefits system, could be: economically sustainable; as redistributive as the current one; almost as poverty reducing as the one in force (or more in some dimensions), and a generator of greater welfare.
Keywords: C60; D31; D63; H20; H24; I3; 330; basic income; redistribution; inequality; progressivity; poverty; welfare; microsimulation; EUROMOD